Stangeland, Addie (audio interview #4 of 5) - Stangeland, Addie (b. 5/10/1902 - d. 5/16/1998); Cleary, Cindy, interviewer
INTERVIEW DESCRIPTION - This is the fourth of five interviews with Addie Stangeland conducted in the bedroom of her daughter's home, where she living. The interview was frequently disturbed by movements of the family in the background. Stangeland was comfortable with the interview process, although she had a hearing problem and questions often had to be repeated. She spoke freely and enjoyed the time with the interviewer. A portion of the interview was mistakenly taped over and so a fifth interview was scheduled to retrieve the lost information. 7/24/1980